INOVASI KUALITAS PENDIDIKAN MELALUI EVALUASI PEMBELAJARAN SENI TARI BERBASIS MEDIA DIGITAL INTERAKTIF - Gyavani Lugwensa; Fuji Astuti; Yuliasma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Dance education in schools plays an important role in developing students’ creativity, aesthetic appreciation, and character. However, its implementation still faces various challenges, such as limited learning media, less varied teaching methods, and low student engagement. This article aims to evaluate dance learning based on interactive digital media as an innovative effort to improve the quality of education. The research method employed is evaluative research with a qualitative descriptive approach, including observation, interviews, and analysis of learning documentation. The evaluation results indicate that the use of interactive digital media can enhance students’ learning motivation, understanding of dance movement materials, and active participation in the learning process. In addition, interactive digital media facilitate teachers in delivering learning materials in a more engaging and contextual manner. Therefore, the evaluation of dance learning based on interactive digital media can serve as a foundation for developing innovative and sustainable learning strategies to improve the quality of arts education in schools. Keywords: learning evaluation, dance education, interactive digital media, educational innovation.